2021
DOI: 10.1021/acsphotonics.1c00235
|View full text |Cite
|
Sign up to set email alerts
|

Single Particle Cathodoluminescence Spectroscopy with Sub-20 nm, Electron-Stable Phosphors

Abstract: Lanthanide-doped nanophosphors have emerged as promising optical labels for high-resolution, "multicolor" electron microscopy. Here, we develop a library of eleven unique lanthanide-doped nanophosphors with average edge lengths of 15.2 ± 2.0 nm (N = 4284). These nanophosphors consist of an electron stable BaYF 5 host lattice doped at 25% atomic concentration with the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…There are several articles in the literature devoted to the optical properties of BaYF 5 doped with Yb 3+ , Ho 3+ , Er 3+ , and Tm 3+ . Although the photoluminescent and radioluminescent properties of transparent glass ceramics containing BaYF 5 :Pr 3+ nanocrystals have been studied, Karbowiak and Cichos and Fedorov et al question the existence of BaYF 5 . Indeed, the BaF 2 –YF 3 phase diagram does not feature the BaYF 5 compound, and one can expect the formation of a Ba 0.5 Y 0.5 F 2.5 solid solution. , Since BaYF 5 is more widely known in the literature, we decided to use this formula instead of Ba 0.5 Y 0.5 F 2.5 .…”
Section: Introductionmentioning
confidence: 99%
“…There are several articles in the literature devoted to the optical properties of BaYF 5 doped with Yb 3+ , Ho 3+ , Er 3+ , and Tm 3+ . Although the photoluminescent and radioluminescent properties of transparent glass ceramics containing BaYF 5 :Pr 3+ nanocrystals have been studied, Karbowiak and Cichos and Fedorov et al question the existence of BaYF 5 . Indeed, the BaF 2 –YF 3 phase diagram does not feature the BaYF 5 compound, and one can expect the formation of a Ba 0.5 Y 0.5 F 2.5 solid solution. , Since BaYF 5 is more widely known in the literature, we decided to use this formula instead of Ba 0.5 Y 0.5 F 2.5 .…”
Section: Introductionmentioning
confidence: 99%
“…The use of a higher repetition-rate laser, for example, from 300 kHz in this study to several MHz, would increase the sampling rate by an order of magnitude. Using a field-emission gun as a brighter electron source in scanning TEM (STEM) that is conventional with a high current density, tr-CL can be mapped with a spatial resolution reaching approximately 10 nm. , The recent study, published while this work was under review, reported the implementation of tr-CL in STEM with a time resolution of sub-nanoseconds, demonstrating a higher sampling rate (2 MHz) and smaller probe size (12 nm) with the scanning capability …”
Section: Concluding Remarks and Outlookmentioning
confidence: 99%
“…Using a field-emission gun as a brighter electron source in scanning TEM (STEM) that is conventional with a high current density, tr-CL can be mapped with a spatial resolution reaching approximately 10 nm. 24,75 The recent study, published while this work was under review, reported the implementation of tr-CL in STEM with a time resolution of sub-nanoseconds, demonstrating a higher sampling rate (2 MHz) and smaller probe size (12 nm) with the scanning capability. 76 With all the technical upgrades currently available, tr-CL spectroscopy coupled with UEM would allow for tracking energy-conversion processes in single-photon sources and single quantum dots.…”
Section: Concluding Remarks and Outlookmentioning
confidence: 99%
“…Therefore, CL has higher spatial resolution on the submicron to nanometer scale, providing richer information about the morphology, and ultrastructural and optical characteristics. [6][7][8] There have been numerous living examples using CL microscopic analysis, such as monitoring the phase separation and degradation of halide perovskite materials, 9 the immunoprotein label in biological imaging, 10 and analyzing the luminescence lifetime of Mn 2+ dopants. 11 On the other hand, field emission displays (FEDs) based on CL technology have numerous advantages of low consumption, quick response, high color tunable ability, etc., and are regarded as a new generation of displays.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, CL has higher spatial resolution on the submicron to nanometer scale, providing richer information about the morphology, and ultrastructural and optical characteristics. 6–8 There have been numerous living examples using CL microscopic analysis, such as monitoring the phase separation and degradation of halide perovskite materials, 9 the immunoprotein label in biological imaging, 10 and analyzing the luminescence lifetime of Mn 2+ dopants. 11…”
Section: Introductionmentioning
confidence: 99%